The Medieval Slavonic Reception of Maximus the Confessor’s Circle – Center – Radii Analogy - Cvetković, Vladimir (De Medio Aevo, 2024)
The paper contends that certain circle diagrams discovered in 14th-century Slavonic medieval manuscripts of Dorotheus of Gaza’s Instructions, crafted during the Palamite controversy, are influenced by the concepts of Maximus the Confessor. The paper offers an in-depth analysis of select Slavonic diagrams originating from Serbian monasteries in the final decades of the 14th century. It begins by examining simple diagrams wherein the circle’s center represents God, and the radii represent created beings moving towards God, then progresses to investigate more intricate diagrams. These complex diagrams include circle or square shaped center, outer circumference, concentric rings, multicolored radii and twisted cruciform bands. It is further argued that these new diagramatic elements are employed to visualize complex ideas such as the Holy Trinity as differentiations in unity, the ontological limit of creation set by divine providence, the triadic structure of logoi of beings and the double movement of procession and reversion.